A Spatial Approach to Energy Economics - Juan Moreno-Cruz; M. Scott Taylor (Center for Economic Studies and ifo Institute (CESifo), 2013)
We develop a spatial model of energy exploitation where energy sources are differentiated by their geographic location and energy density. The spatial setting creates a scaling law that magnifies the importance of differences across energy sources. As a result, renewable sources twice as dense, provide eight times the supply; and all new non-renewable resource plays must first boom and then bust. For both renewable and non-renewable energy sources we link the size of exploitation zones and energy supplies to energy density, and provide empirical measures of key model attributes using data on solar, wind, biomass, and fossil fuel energy sources. Non-renewable sources are four or five orders of magnitude more dense than renewables, implying that the most salient feature of the last 200 years of energy history is the dramatic rise in the use of energy dense fuels.
Keywords: Q41; 330; energy; renewables; agglomeration